Optimalisasi Penggunaan Buku Cerita Bergambar untuk Meningkatkan Minat Membaca Siswa MI - Nova Emila, Fitria; Fajri, Zaenol (Jurnal Ilmiah Profesi Pendidikan, 2025)
The low reading interest among Madrasah Ibtidaiyah (MI) students remains a significant challenge in education, as it can negatively impact their academic achievement and literacy development. One way to enhance students' reading interest is by optimizing picture storybooks and combining engaging text and illustrations to stimulate students' imagination and comprehension. This study employed a Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, conducted in two cycles, each involving planning, action, observation, and reflection stages. Data collection techniques included structured observations, interviews, and anecdotal records with third-grade students of MI Miftahul Ulum Pancoran Bondowoso. The results showed that using picture storybooks significantly increased students' reading interest. In the first cycle, some students began to show interest in the illustrations, although their active engagement in reading and discussion remained low. After improvements in the second cycle, including selecting books that better-matched students' interests and applying cooperative learning strategies, student involvement in reading, discussion, and story comprehension increased significantly. Observations, interviews, and anecdotal records indicated an improvement in students' engagement scores from "fair" to "good" and "excellent categories. Optimizing the use of picture storybooks effectively enhances MI students' reading interest. Picture storybooks attract students' attention cre, create a more enjoyable learning environment, and foster a positive reading culture from an early age.